Teacher Support of Co- and Socially-Shared Regulation of Learning in Middle School Mathematics Classrooms - Quackenbush, Melissa; Bol, Linda (Frontiers in Education, 2020)
Social influences on classroom learning have a long research tradition and are critical components of self-regulated learning theories. More recently, researchers have explored the social influences of self-regulated learning in cooperative learning contexts. In these settings, co-regulation of learning and socially-shared regulation of learning strategies have been aligned with self-regulated learning theory. However, without specific training or structure, teachers are not likely to explicitly integrate SRL strategies into their teaching. We use case studies to better understand how Zimmerman's theory of self-regulated learning (2008) and Hadwin's conceptual framework of socially-shared regulation of learning (2018) emerge from teachers' support of student-centered instruction. We purposely selected two proficient teachers for more extensive observations focused on student behaviors in teams. The observation instruments afford us a means of advancing research and practice with respect to how teamwork may elicit self- and socially-shared regulation of learning strategies. Consistent with previous findings, the teachers we observed seem to have made many pedagogical moves to explicitly prompt self- and team monitoring of learning during engagement with course content yet provided fewer opportunities for students to think through the planning and evaluation processes. These findings suggest the cooperative learning model implemented in these classrooms provides support for students' co- and socially-shared regulation of learning.